Determinan Pendapatan Pedagang Pasar Tradisional dan Strategi Peningkatannya di Pasar Talang Banjar Kota Jambi - Anggita Andriyati; Muhammad Rachmad R; Jaya Kusuma Edy (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the factors that influence the income of market traders at Talang Banjar Market, Jambi City, and to formulate income improvement strategies through SWOT analysis. The research employed a quantitative method with data collected through questionnaires and interviews with market traders. The data were analyzed using multiple regression analysis with the assistance of Eviews software, as well as SWOT analysis to formulate business development strategies. The results of the study show that the variables of capital, labor, and working hours have a significant effect on traders’ income, while the type of merchandise has no significant effect. Based on the SWOT analysis, the position of traders at Talang Banjar Market is located in Quadrant I, which indicates that the appropriate strategy to apply is an aggressive (S-O) strategy. This strategy emphasizes the utilization of internal strengths—such as product quality, competitive pricing, and customer service—to seize external opportunities, including government policies and broad market potential.